Exploring healthcare providers’ perspectives on type 1 diabetes management in rural and resource-limited settings - Giri, Subhajit; Patil, Shailaja S.; Ganganahalli, Praveen; Udgiri, Rekha; Senapati, Adyasha (International Journal of Research in Medical Sciences, 2025)
Background: Type 1 diabetes mellitus (T1D) is a chronic autoimmune condition requiring lifelong insulin therapy and comprehensive care. In India, especially in rural and resource-limited settings, challenges in availability of insulin, provider training, patient education, and psychosocial support persist. Most studies emphasize patient experiences; however, healthcare providers’ perspectives remain underexplored. Methods: A mixed-methods cross-sectional study was conducted among 82 healthcare providers, including endocrinologists, nurses, diabetes educators, and primary care physicians. Data were collected using structured questionnaires (quantitative) and semi-structured interviews/focus group discussions (qualitative). Quantitative data were analyzed using descriptive statistics, while qualitative transcripts underwent thematic analysis. Findings were integrated through convergent analysis. Results: Among participants, 85% identified irregular insulin supply and affordability as major barriers, while 78% reported low patient awareness and literacy. Insufficient provider training (70%) and lack of systematic follow-up (65%) were also highlighted. Only 30% reported regular interdisciplinary coordination, and just 20% addressed psychosocial issues during consultations. Qualitative themes reinforced these findings, highlighting four domains: (1) systemic care barriers (supply shortages, workload, inadequate infrastructure), (2) patient engagement challenges (low literacy, stigma, myths), (3) limited team-based care (poor referrals, lack of formal coordination), and (4) neglected psychosocial support (absence of counseling, unmet family needs). Conclusions: Providers face significant systemic, educational, and psychosocial challenges in managing T1D in rural India. Strengthening provider training, ensuring insulin availability, enhancing patient education, establishing multidisciplinary networks, and integrating psychosocial services are critical to improve outcomes.